Designing and Developing Rechargeable Aluminium-Ion Battery using Graphite Coated Activated Charcoal Corncob as Cathode Material - F. Fitriah; A. Doyan; S. Susilawati; S. Wahyuni (Jurnal Pendidikan Fisika Indonesia)
One of the renewable energy storage systems that can be used today is the aluminum ion battery. In this study, aluminum foil was used as anode, polyetylene polyprophylene (PE/PP) as separator, electrolyte from AlCl3/[EMIm]Cl and graphite coated corncob, an activated charcoal, as cathode. Coating method of cathode materials was done by mixing both graphite and activated charcoal with varied composition 1:0.5, 1:1, 1:1.5, and 1:3. The coating process began by mixing the graphite and corncob with ethanol as a solvent for six hours, then heating in an oven at 80 °C for three days, gradual drying in a furnace at 350 °C for five hours and sintering at 600 °C for six hours. From this research, SEM results showed that carbon particles were evenly distributed, with spherical particles. The spherical shape was the main requirement of carbon formation in order to produce high energy. Based on the results, battery potential was 2.54 V with average of optimal capacity at a ratio of graphite and corncob activated charcoal 1:1.5 was 83.067 mAh/g. The highest efficiency was also at a ratio of 1:1.5 of 97.20%, because at this ratio, there was an increasing in percentage of element C 91.74%, greater than the percentage of element C on the other three cathode samples.